ANALISIS KADAR KLORIN (Cl2) SEBAGAI PEMUTIH PADA RUMPUT LAUT (Eucheuma cottonii ) YANG BEREDAR di LAMPUNG - Samsuar Samsuar; Febri Mariana; Merinda Setyowati (JFL : Jurnal Farmasi Lampung, 2017)
Seaweed (Eucheuma cottonii) is one of sea product which have promising economic value, because it can be used for carragenan manufactures. In industrial and commerce, carragenan can be used as ingredients for biotechnology, food, pharmacy and cosmetic industry. The purpose of this research is to determine chlorine contain in seaweed at the first and second submersions. There are nine samples of seaweed which are examined at UPTD Hall of Lampung Health Laboratory and Fharmacy Laboratory of UTB Lampung with using titration method. The results of chlorine content on nine seaweed samples at the first immersion in A sample of 0.027%, in sample B of 0.019%, in sample C of 0.034%, in sample D of 0.008%, F samples of 0.079%, samples H by 0.027%. In sample E, sample G and sample I when analyzed there is no chlorine content. The content of chlorine on the second immersion is in sample A of 0.019%, in sample B of 0.015%, in sample C of 0.03%, in sample D of 0.008%, and F sample 0.057%. In the H sample the chlorine levels on the second immersion become negative or disappear. Keyword : Seaweed, chlorine and titration